Shonen note : boy soprano. 2 - Kamatani, Yuhki (Kodansha USA Publishing, LLC, 2023)
"Now that Yutaka has officially decided to join the city opera, he's cast in a leading role in the ghost story The Turn of the Screw. Meanwhile, school choir president Betsuyaku struggles to prove that he and his choir are capable of winning the gold prize in the NHK All-School Choir Competition. But can he bring the choir together to achieve greatness, or will he alienate all of its members?"--